Weekly paclitaxel in escalating doses in a patient with anthracycline-resistant, triple-negative, metastatic breast cancer with severe liver dysfunction - Gupta, Ajay (Indian Journal of Medical and Paediatric Oncology, 2012)
Liver dysfunction in a patient with anthracycline-resistant breast cancer and liver metastases with poor performance status (PS) represents a serious situation. Taxanes are the drugs of choice, but once the transaminase enzyme levels are raised more than 10-times the upper limit of normal (>10 ULN), paclitaxel administration is contraindicated. We present the report of one such case who had a gratifying response to escalating doses of weekly paclitaxel thus suggesting that even patients with severe liver dysfunction can derive benefits from such a strategy. The patient, a 54-year-old lady with breast cancer metastatic to the liver and bones and previous receipt of anthracycline-based therapy, presented to us with a PS of 3. Her liver functions (LFT) were: serum bilirubin 2.2 mg% (0.3-1.1 mg%), aspartate aminotransferase 375 IU/L (0-25 IU/L), alanine aminotransferase 369 IU/L (0-35 IU/L) and alkaline phosphatase 363 IU/L (38-126 IU/L). She was started on weekly paclitaxel 20 mg/m 2 and zoledronate. After the first dose, the LFTs rose marginally but the skin lesions stabilized. Dose was subsequently escalated to 40 mg/m 2 . At the end of the 10th week, her PS improved to 1 and the disease showed a partial response. LFTs improved markedly. However, 5 days after the administration of the 13 th dose, the disease progressed and paclitaxel had to be discontinued. It is possible to derive maximum palliative benefit with escalating doses of weekly paclitaxel even in patients whose liver functions are deranged with transaminase levels (>10 ULN) and in whom conventional administration of paclitaxel is contraindicated.
Keywords: Liver dysfunction; metastatic breast cancer; paclitaxel; severe liver dysfunction